2008
DOI: 10.1016/s1808-8694(15)30585-1
|View full text |Cite
|
Sign up to set email alerts
|

Nasolabial cyst: presentation of a clinical case with CT and MR images

Abstract: The nasolabial cyst is an uncommon non-odontogenic cyst that develops in the lower region of the nasal ala; its pathogenesis is uncertain. This lesion grows slowly and measures between 1.5 and 3 cm; it is characterized clinically by a floating tumefaction in the nasolabial sulcus, which elevates the upper lip. The diagnosis is based on the clinical findings and, if necessary, image exams. This paper reports a case of a white 48-year-old Brazilian female patient that presented a firm tumor in the left ala of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
23

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 14 publications
1
21
0
23
Order By: Relevance
“…In addition, Choi et al [12] reported the occurrence of eight cases of nasolabial cyst over a period of only 1 year and suggested that these cysts may be more common than previously thought. A predominance of nasolabial cysts among females has been reported [5,32], with a female/male ratio ranging from 2.2:1 to 6.1:1 [11][12][13]. Most cases are diagnosed in the fourth and fifth decades of life [3,12,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Choi et al [12] reported the occurrence of eight cases of nasolabial cyst over a period of only 1 year and suggested that these cysts may be more common than previously thought. A predominance of nasolabial cysts among females has been reported [5,32], with a female/male ratio ranging from 2.2:1 to 6.1:1 [11][12][13]. Most cases are diagnosed in the fourth and fifth decades of life [3,12,32].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of their origin, nOCs tend to grow slowly in size, possibly in response to an increase in luminal hydrostatic pressure [5]. Some lesions may resolve spontaneously, such as palatal cysts of the newborn [6,7], whereas others such as thyroglossal duct cysts present a high recurrence rate if not treated aggressively [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Nasolabial cysts do not present any finding on plain radiographs. Computed Tomography and Magnetic Resonance Imaging can reveal the extent and relation of lesion to surrounding structures [3][4][5][6]. Histopathologically the cyst is lined with pseudostratified columnar epithelium and occasionally a stratified squamous epithelium [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…1951'de Ra o, nazolabial kist is mi ni ilk ola rak kullan mış tır ve söz ko nu su kist ler bu isim le ad lan dı -rıl ma ya de vam edil mek te dir. 4,5 1953'te Kles tadt nazolabial kist le rin or ta-la teral na zal çı kın tı ve mak sil lar çı kın tı füz yon hat tın -da yer alan em bri yo lo jik ek to der mal epi tel ar tı ğın dan ge liş ti ği ni ile ri sür müş tür. 1920'de ise Brug ge man bu kist le rin em bri yo lo jik dö nem de naso lak ri mal ka na lı oluş tu ran ve na sal-mak sil ler şiş-lik le rin ara sın da bu lu nan na so lak ri mal çen ti ğin ön alt par ça sın da ki em bri yo nel hüc re ar tık la rın dan geliş ti ği fik ri ni or ta ya at mış tır.…”
unclassified
“…4 T1 ve T2 ağır lık lı se kans lar da hi pe rin tens sin yal özel-li ği sap ta mış lar ve T1 ağır lık lı se kans lar da ki hi perin tens gö rü nü mün kis tin pro te in içe ri ği ne bağ lı ol du ğu nu be lirt miş ler dir. Bi zim ol gu muz da ise nazolabial kist, T1 ağır lık lı se kans lar da ha fif hi pe rintens ve T2 ağır lık lı se kans lar da hi pe rin tens sin yal özel li ği gös ter miş tir.…”
unclassified